2003
DOI: 10.1097/00063110-200309000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lunar cycle on temporal variation in cardiopulmonary arrest in seven emergency departments during 11 years

Abstract: Contrary to the traditional belief that more cardiopulmonary resuscitations occur during the full moon, we were unable to identify a significant effect during full moon days. However, there were on average 6.5% fewer cardiopulmonary resuscitations during new moon days than other days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…This study showed that more ACS cases occur within the period of new moon. Even more, the occurrences of cardiopulmonary resuscitations did not revealed relationship with the lunar activity [19]. This suggests that different medical conditions have different sensitivity to lunar activity and possibly other environment conditions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This study showed that more ACS cases occur within the period of new moon. Even more, the occurrences of cardiopulmonary resuscitations did not revealed relationship with the lunar activity [19]. This suggests that different medical conditions have different sensitivity to lunar activity and possibly other environment conditions.…”
Section: Discussionmentioning
confidence: 88%
“…(1)) was used [19]. The drawback of DFT is that one cannot observe the change in spectral density over time unless sequentially computing DFT.…”
Section: Spectral Analysis Of the Magnetometer Datamentioning
confidence: 99%
“…Also there is a cultural belief in more than ten percent of the Western European population, that the moon affects health care and is assumed to have a negative effect on procedures, as the occurrence of Friday 13 th is supposed to be associated with worsened outcome [3]. Studies have been performed to analyze the effect of the lunar cycle on birth rates [4], emergency department presentations [5], cardiopulmonary resuscitations [6,7] and psychiatric disorders [8]. Surgery specific studies looked into the incidence of postoperative hemorrhage [9,10], intraoperative blood loss [11], morbidity and mortality after lung and breast cancer surgery [12,13] and quality of radical cystectomy for bladder cancer [14] in relation to the lunar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many published reports of the impact of the Moon's phases on the occurrence of cardiovascular diseases, psychiatric disorders, rheumatologic disorders, birth rates, the risk of sudden cardiac death and the number of emergency department visits or hospital admissions. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) In the vast majority, a link was not identified. Even the shifts of lunar phases are often considered a marker of oscillation of the gravitational field of the Moon; in fact, there is no direct relationship between these natural phenomena.…”
Section: Introductionmentioning
confidence: 99%